UNJUK KERJA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) 26,4 KWP PADA SISTEM SMART MICROGRID UNUD - Gunawan, N. Surya; Kumara, I. N. Satya; Irawati, Rina (Jurnal SPEKTRUM; Vol 6 No 3 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i03.p01, 2019)
Smart Microgrid System of Udayana University is collaboration project between Ministry of Energy and Mineral Resources with Udayana University. The system consist of 26.4 kWp Solar Power Plant, 5 kWp Wind Turbine, 20 kWp Diesel Generator, 192 kVAh battery and connected with a low voltage distribution network 220/380 V. This paper discusses performance of the solar power plant with HelioScope. The simulation results will be compared with the real energy production from solar power plant The simulation results is 43,055.4 kWh per year. Whereas the real production is 3,948.28 kWh, lower by 4,107.4 kWh or 9.53% than the simulation. Factors that influence the difference are shade, the cleanliness of solar modules and orientation of the solar modules.